Rancang Bangun Aplikasi Inventory Material Jasa Pelaksana Kontruksi PT. Bawan Permai Group Berbasis Website - Laola, Veni; Widiatry, Widiatry; Licantik, Licantik (Universitas Palangka Raya, 2021)
Bawan Permai Group is a company engaged in the procurement of construction services (contractor). So a computerized system is created which aims as a medium that facilitates and assists the company in managing, recording or controlling the inventory of construction services materials. The methodology used in making this application, namely Waterfall According to Summerville in 2011, which has stages, namely Requirements Definition which is carried out by making Flowcharts of the old system and the new system. System and Software Design is made by making Data Flow Diagrams (DFD) and Entity Relationship Diagrams (ERD). Implementation and Unit Testing is carried out by the realization of the system in the previous stage into the PHP programming language and MySQL database.Integration and System Testing is retested using Blackbox Testing. Blackbox Testing focuses on the functional specifications of the program. After testing, the results can be seen, namely the system can run properly. However, this application must always be monitored, developed and updated so that information can be conveyed properly and according to user needs.